Peripheral blood dendritic cells and monocytes are differently regulated in the elderly - Della Bella, Silvia (Clinical immunology (Orlando, Fla.), 2007)
Dendritic cells (DCs) are the single most central player in all immune responses. To assess whether DC alterations may contribute to the immune dysregulation that affects the elderly, we investigated the effects of ageing on DCs. We analyzed the number, phenotype and function of peripheral blood DCs from 70 healthy subjects aged 20-92 years by using flow cytometric methods that allow cell characterization directly in whole blood samples. We demonstrated that the number of myeloid DCs progressively declines with age. This finding was accompanied by a decrease of CD34+ precursors and increase of circulating monocytes, suggesting that the entire differentiation process of antigen presenting cells is partially dysregulated in the elderly. DCs from aged individuals also appeared to have a more mature phenotype and impaired ability to produce IL-12 upon stimulation. These results may help to clarify the contribution of innate immunity to the development of immunosenescence